Effect of Natural Compounds on Insulin Signaling - Paoli, Paolo; Caselli, Anna; Camici, Guido; Cirri, Paolo (Current Medicinal Chemistry, 2015)
Results of several epidemiological studies have indicated that diabetes mellitus will become a global epidemic in the next decades, being more than 400 million the human subjects in the world affected by this disease in the 2030. Most of these subjects will be affected by type 2 diabetes mellitus (T2DM) whose diffusion is mainly related to excessive caloric upload, sedentary life and obesity. Typically, the treatment for T2DM is diet, weight control, physical activity or hypoglycaemic and/or lipid-lowering drugs. Unfortunately, these drugs often show low effectiveness or adverse side effects, thereby forcing patient to discontinue medical treatment. Nevertheless traditional medicine suggests the use of several formulations or medicinal foods to treat T2DM. Most of them are characterized by safety, low cost, effectiveness, and good availability. Before the advent of modern pharmacology, these remedies were used to treat diabetes and obesity or prevent their onset. Today, we know that their effectiveness is due to the presence of several bioactive compounds able to influence insulin signaling pathway and cellular metabolism. In the last decades, many efforts have been carried out to clarify their action mechanism. Here we provide a classification of the natural compounds that stimulate the insulin pathway, highlighting their effectiveness in controlling glycaemia on diabetic animal models or improving insulin signaling in cellular systems.
Keywords: PTP1B inhibitors